Polychlorinated dibenzo-p-dioxins, dibenzofurans and polychlorinated biphenyls in polar bear, penguin and south polar skua - KUMAR, K.; KANNAN, K.; CORSOLINI, S.; EVANS, T.; GIESY, J. P.; NAKANISHI, J.; MASUNAGA, S. (Environmental Pollution, 2002)
Concentrations of 2378-substituted polychlorinated dibenzo-p-dioxins (PCDDs), dibenzofurans (DFs) and non- and mono-ortho-substituted polychlorinated biphenyls (dioxin-like PCBs) were measured in livers of polar bears from the Alaskan Arctic and in eggs of Adelie penguin and south polar skua and weddell seal liver, fish and krill from Antarctica. This is one of the first reports to document the concentrations of PCDDs/DFs in polar bear livers from Alaska, and in penguin and skua eggs from Antarctica. Concentrations of total PCDD/DFs in livers of polar bears ranged from 8 to 66 (mean: 26) pg/g, on a lipid weight basis. Concentrations of total PCDD/DFs in Antarctic samples were in the increasing order on a lipid weight basis; weddell seal liver (8.9 pg/g)>penguin eggs (30 ng/g)>seal liver (57 ng/g)>fishes (6.2 ng/g)>krill (0.9 ng/g). Concentrations of 2378-tetrachlorodibenzo-p-dioxin equivalents (TEQs) calculated based on the WHO TEFs were higher in the eggs of polar skua (mean: 344; range: 220-650 pg/g, lipid wt.) from Antarctica than in polar bear livers from Alaska (mean: 120; range: 69-192 pg/g). In general, concentrations of PCDFs were greater than those of PCDDs in polar organisms. 23478-PeCDF is one of the dominant congener found in several samples. Concentrations of TEQs in polar bear livers and skua eggs were close to those that may cause adverse health effects. Dioxin-like PCBs, particularly, non-ortho coplanar PCBs were the major contributors to TEQ concentrations in penguin and skua eggs whereas mono-ortho PCBs accounted for a major portion of TEQs in polar bear livers. © 2002 Elsevier Science Ltd. All rights reserved.